Does public health policy quality foster state innovation capacity? Evidence from a global panel data - Ji, Xiaoyi; Gao, Ling; Liu, Huan; He, Shengyu; Zhu, Baoqing; Chow, Cheng; Chen, Jieqiong; Lu, Zhipeng; Li, Li (Frontiers in Public Health, 2022)
The design and implementation of public health policy may shape state innovation capacity with governance effectiveness, political stability, and government integrity. Previous studies, however, failed to incorporate these relationships simultaneously. This study aims to combine two distinct scholarships to examine whether the quality of policies in the public health sector contributes to state innovation capacity. We extracted data from the WHO international health regulatory dataset covering the WHO Member States between 2010 and 2017 to investigate the relationship (N = 145). Our fixed-effects models and regression discontinuity design (RDD) suggest a positive impact of public health policy quality on state innovation capacity. There are several contributions to the study of the relationship between public health and innovation in this study. Firstly, it fills a theoretical void concerning the relationship between policy development and implementation in the public health sector and country-specific innovations. Second, it provides an empirical quantitative analysis of policy quality in the public health sector. Third, this study contributes evidence that public health plays an important role in fostering state innovation beyond urbanization, investment in science and technology, and foreign trade. Furthermore, our quasi-experimental evidence found that this mechanism may be significant only between the more politically stable countries and the most politically stable countries. These contributions have empirical implications for governments across the world that seek to balance public health and innovation capacity in the context of the post-pandemic era.